2021
DOI: 10.1159/000512473
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant <b><i>Pseudomonas Aeruginosa</i></b> Keratitis with Hyphaema

Abstract: <b><i>Purpose:</i></b> To report a case of recalcitrant pseudomonas keratitis with a rare presentation of hyphaema. <b><i>Observation:</i></b> A 45-year-old female was noted to have contact lens-related pseudomonas keratitis with hyphaema. The organism was refractory to multiple antibiotics and only responded to Tazocin eye drops. <b><i>Conclusion and Importance:</i></b> Hyphaema is a rare presentation in bacterial keratitis and could repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recalcitrant keratitis caused by P. aeruginosa is a serious and potentially blinding condition. The aggressive nature of the organism coupled with its evolving multidrug resistance is an important cause of ocular morbidity (Chan et al 2021). This case report illustrates the importance of the initial treatment in bacterial keratitis.…”
Section: Discussionmentioning
confidence: 81%
“…Recalcitrant keratitis caused by P. aeruginosa is a serious and potentially blinding condition. The aggressive nature of the organism coupled with its evolving multidrug resistance is an important cause of ocular morbidity (Chan et al 2021). This case report illustrates the importance of the initial treatment in bacterial keratitis.…”
Section: Discussionmentioning
confidence: 81%
“…Studies on rabbits in vivo used various concentrations of gentamicin (1.6, 3, 5 &13 mg mL -1 ) to treat P. aeruginosa keratitis with mixed therapeutic outcome (Punitan et al, 2019, Rootman and Krajden, 1993, Fruchtpery et al, 1995, Silbiger and Stern, 1992, Gupta et al, 1995, Kowalski et al, 2013, Ahmad et al, 1977. One case study showed that the treatment with 14 mg mL -1 gentamicin failed even though the P. aeruginosa strains isolated from human cornea were identified as sensitive to this antibiotic (Chan et al, 2021). Some of the concentrations used in mentioned studies were cytotoxic because it was found that as little as of 3 mg mL -1 of this antibiotic is cytotoxic in human corneal epithelial cells in vitro (Tsai et al, 2010) and impairs the wound healing in rabbits in vivo (Stiebel-Kalish et al, 1998).…”
Section: Discussionmentioning
confidence: 99%